Pemetaan Data Hadis Melalui Teknologi Blockchain: Upaya Menjaga Keotentikan dan Keamanan Informasi Hadis - Sulhayani Sulhayani (Yayasan Albahriah Jamiah Indonesia, 2025)
The authenticity of hadith, the second most important source of Islamic teachings after the Quran, has become a crucial issue in the digital era, where the massive and unverified flow of information opens up opportunities for distortion, manipulation, and duplication of hadith data in cyberspace. Challenges to the validity of hadith data require a digital mapping and verification system capable of ensuring the integrity of the sanad (transmitted text) and matan (transmitted text) in a multi-layered manner. This study aims to develop a blockchain-based hadith data mapping model as an innovative effort to maintain the authenticity, transparency, and security of hadith information in the digital ecosystem. Using a qualitative descriptive-analytical method, this study relies on data sourced from the latest academic literature on hadith digitization and blockchain technology. Data analysis was conducted using a content analysis and conceptual synthesis approach to formulate a conceptual model for hadith mapping that is adaptive to blockchain characteristics. The results show that the application of blockchain technology can provide a decentralized, immutable, and transparent hadith data storage and distribution system, where each blockchain serves as an authentic record of sanad and matan transactions that cannot be changed or falsified. This technology enables chronological and verifiable tracing of the origins of hadith and strengthens smart contract-based digital validation mechanisms. Theoretically, this research enriches the body of digital hadith knowledge by integrating cutting-edge technological paradigms into the study of hadith authenticity. Practically, the results provide new directions for developing a more secure, credible, and future-oriented implementation model for a digital hadith literacy system.